CONTEXT AND SOCIAL VALUE SOCIAL VALUES IN HAMKA'S ANTHOLOGY OF SHORT STORIES IN THE VALLEY OF LIFE: SOCIOLOGY IAN WATTS LITERATURE - Antika, Nurfadila; Mahmudah, Mahmudah; Tufli, Muhammad Alfian (Media Inovasi Pendidikan dan Publikasi, 2025)
This study aims to describe the social context, social values, and the role of literature as a reflection of society in Hamka's anthology of short stories In the Valley of Life using Ian Watt's literary sociology approach. This research focuses on three main problem formulations, namely: (1) how the social context is depicted in the short stories, (2) how social values are represented, and (3) how literature acts as a reflection of society. This research uses descriptive qualitative method with literature study technique. The results show that the short stories in this anthology reflect the social conditions of Minangkabau society at that time, such as the cultural system, social inequality, and the dynamics of family life. The social values found include the importance of solidarity, sacrifice, and responsibility towards the family. In addition, these short stories also feature relevant social criticism, making Hamka's work a medium to describe the social reality of society. Through Ian Watt's literary sociology approach, this research provides new insights into Hamka's contribution in shaping social awareness and enriches the understanding of the relationship between literature and society